Factors influencing the effectiveness of colonoscopy - Mustikawati; Sodikin (Proceedings Series on Health & Medical Sciences, 2020)
Colonoscopy is one of the most widely-used procedures for diagnostic examination and treatment of colorectal diseases, either benign or malignant. Colonoscopy results are influenced by several factors such as current medical history, history of drug use, history of accompanying illnesses, and procedures performed. To analyze the factors which affectiverness the results of colonoscopy among the undergoing patients in Regional Public Hospital of Banyumas. The method used was observational analytic with a cross sectional approach. From the consecutive sample selection, it gave 76 respondents. The analysis was done using Univariate analysis with frequency distribution test, bivariate with chi square test and multivariate with multiple logistic regression test. Most of the respondents (51 respondents, 67.1%) aged 46-65 years and most of them were female (41 or 53.1%), they were dominated by high school graduates (56 or 73.7%), and the dominant occupation status was undemployed (31 or 40.8%). The results of the chi square test showed that there was an effect of current disease history, namely complaints / indications for colonoscopy examinations (p 0.011), drug use (p 0.021),accompanying disease history (p 0.003), and implementation procedures (p 0.000) on colonoscopy results. The results of multiple logistic regression showed that the factor that mostly influences the colonoscopy results was the length of preparation time (1-2 days of preparation).In conclusion current medical history, drug use history, accompanying medical history, and procedure administration significantly influence the colonoscopy outcome. And the most influencing factor is the length of preparation time (1-2 days of preparation).